Cultural Heritage Between Identity and Extinction (Comprehensive Journal of Science, 2026)
National identity in any society is rooted in the customs, traditions, and rituals practiced by the members of that social group, the purpose of which is to express their customs and traditions in times of joy and sorrow. This represents the cohesion of a society’s social fabric and its pride in its social environment, through this heritage passed down from generation to generation. This heritage takes two forms: tangible heritage, which includes all material objects such as clothing, headwear, footwear, food, housing, or items used in religious rituals; and intangible heritage, such as myths, poetry, and stories.
Keywords: cultural heritage; national pastime; intangible heritage